Presentation of TRPM1-Associated Congenital Stationary Night Blindness in Children - Miraldi Utz, Virginia (JAMA Ophthalmol, 2018)
IMPORTANCE: Congenital stationary night blindness (CSNB) implies a stable condition, with the major symptom being nyctalopia present at birth. Pediatric clinical presentation and the course of different genetic subtypes of CSNB have not, to our knowledge, been well described in the era of molecular genetic diagnosis. OBJECTIVE: To describe the presentation and longitudinal clinical characteristics of pediatric patients with molecularly confirmed TRPM1-associated complete CSNB (cCSNB). DESIGN, SETTING, PARTICIPANTS: This study was conducted at the University of Iowa from January 1, 1990, to July 1, 2015, and was a retrospective, longitudinal case series of 7 children (5 [71.4%] female) with TRPM1-associated cCSNB followed up for a mean (SD) of 11.1 (2.8) years. MAIN OUTCOMES AND MEASURES: History, ophthalmologic examination findings, full-field electroretinogram (ffERG) results, full-field stimulus threshold testing results, Goldmann visual field results, optical coherence tomography results, and molecular genetic results were evaluated. Presenting symptoms and signs, the correlation of refractive error with electroretinography, and clinical evolution were analyzed. RESULTS: Seven patients (5 [71.4%] female) presented early in childhood with strabismus (n = 6 [86%]), myopia (n = 5 [71%]), and/or nystagmus (n = 3 [43%]). The mean (SD) age at presentation was 8 (4) months and for receiving a diagnosis by ffERG was 7.3 years, with molecular diagnosis at 9.7 years. The mean (SD) length of follow-up was 11 (2.8) years. The best-corrected visual acuity at the most recent visit averaged 20/30 in the better-seeing eye (range, 20/20-20/60). The mean (SD) initial refraction was −2.80 (4.42) diopters (D) and the mean refraction at the most recent visit was −8.75 (3.53) D (range, −4.00 to −13.75 D), with the greatest rate of myopic shift before age 5 years. Full-field electroretinogram results were electronegative, consistent with cCSNB, without a significant change in amplitude over time. No patient or parent noted night blindness at presentation; however, subjective nyctalopia was eventually reported in 5 of 7 patients (71%). The full-field stimulus threshold testing results were moderately subnormal (−29.7 [3.8] dB; normal −59.8 [4.0] dB). Goldmann visual field results were significant for full I-4e, but constricted I-2e isopter. Eight different mutations or rare variants in TRPM1 predicted to be pathogenic were detected, with 3 novel variants. CONCLUSIONS AND RELEVANCE: Children with TRPM1-associated cCSNB presented before school age with progressive myopia as well as strabismus and nystagmus (but not nyctalopia), with stable, electronegative ffERG results, mildly subnormal full-field stimulus threshold testing results, and a constricted I2e isopter on perimetry. These findings suggest that ffERG and cCSNB genetic testing should be considered for children who present with early-onset myopia, especially in the presence of strabismus and/or nystagmus, and that TRPM1-associated cCSNB is a channelopathy that may present without complaints of night blindness in childhood.